The Impact of Agricultural Sector Development on Employment and Income Inequality using Panel Data Regression Analysis - Setiawan, Alvin; Barokatuminalloh, Barokatuminalloh; Fauzi, Pahrul (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2024)
The level of labor absorption and distribution of community income does not follow the large value of GRDP and investment. This study aims to analyze the effect of development and investment in the agricultural sector on labor absorption and the distribution of income. This study used a quantitative descriptive with secondary data and multiple linear regression analysis. The analysis is divided into two models, the first model is to analyze the impact of development and investment on labor absorption, while the second model is on the distribution of income. The first model shows that agricultural development has a significant effect on labor absorption, while agricultural investment has no significant effect. The second model shows that agricultural development has a significant effect on income distribution while agricultural investment has no significant effect. The implication is that the government implements policies that encourage productivity, as well as equal distribution of supporting facilities.